Transcriptome dynamics in early zebrafish embryogenesis determined by high-resolution time course analysis of 180 successive, individual zebrafish embryos - Rauwerda, Han (BMC Genomics, 2017)
BACKGROUND: Recently, much progress has been made in the field of gene-expression in early embryogenesis. However, the dynamic behaviour of transcriptomes in individual embryos has hardly been studied yet and the time points at which pools of embryos are collected are usually still quite far apart. Here, we present a high-resolution gene-expression time series with 180 individual zebrafish embryos, obtained from nine different spawns, developmentally ordered and profiled from late blastula to mid-gastrula stage. On average one embryo per minute was analysed. The focus was on identification and description of the transcriptome dynamics of the expressed genes in this embryonic stage, rather than to biologically interpret profiles in cellular processes and pathways. RESULTS: In the late blastula to mid-gastrula stage, we found 6,734 genes being expressed with low variability and rather gradual changes. Ten types of dynamic behaviour were defined, such as genes with continuously increasing or decreasing expression, and all expressed genes were grouped into these types. Also, the exact expression starting and stopping points of several hundred genes during this developmental period could be pinpointed. Although the resolution of the experiment was so high, that we were able to clearly identify four known oscillating genes, no genes were observed with a peaking expression. Additionally, several genes showed expression at two or three distinct levels that strongly related to the spawn an embryo originated from. CONCLUSION: Our unique experimental set-up of whole-transcriptome analysis of 180 individual embryos, provided an unparalleled in-depth insight into the dynamics of early zebrafish embryogenesis. The existence of a tightly regulated embryonic transcriptome program, even between individuals from different spawns is shown. We have made the expression profile of all genes available for domain experts. The fact that we were able to separate the different spawns by their gene-expression variance over all expressed genes, underlines the importance of spawn specificity, as well as the unexpectedly tight gene-expression regulation in early zebrafish embryogenesis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-017-3672-z) contains supplementary material, which is available to authorized users.